Village Head Leadership in Implementing the Village Development Movement Program in West Malinau Sub-district, Malinau Regency - Maksuwel Maksuwel; Entang Adhy Muhtar; Heri Wahyudi (Green Publisher Indonesia, 2025)
To realize the Village Building Movement (GERDEMA) in West Malinau District, Malinau Regency, it is necessary to have sensitive Village Head leadership. The Village Head must listen to suggestions and views from the people around him, be an example to others, behave consistently, remain loyal to his promises and to his government, and be able to make decisions in accordance with the ideals and expectations of the community. The purpose of this study is to describe and analyze how Village Head Leadership influences the implementation of the Village Development Movement Program (GERDEMA) in West Malinau District, Malinau Regency. Although leadership problems among Village Heads have been addressed in general, in reality, these issues have not been fully and optimally resolved. The method used is qualitative, aiming to explore and understand the meanings held by individuals or groups regarding social or humanitarian issues. The purpose of this qualitative research is to understand particular situations, events, roles, groups, or social interactions that are considered social problems. The results of the study show that Village Head Leadership in the implementation of the Village Movement Program in West Malinau District is carried out effectively. The Village Head demonstrates good sensitivity, embodies an exemplary spirit that serves as a model, complies well with program implementation in the village, and exhibits leadership and integrity in executing the Village Development Movement (GERDEMA) program.